Medicinal properties and anti-inflammatory components of Phytolacca (Shanglu) - Christian Bailly (KeAi Communications Co., Ltd., 2021)
Phytolacca: (Shanglu) is a well-known traditional herbal medicine that has been used for thousands of years in China. Phytolacca is also used worldwide in different traditional phyto-medicines and homeopathic preparations. The present work reviewed advances in the traditional uses, plant origin, chemical constituents, pharmacology, and medicinal properties of Phytolacca. Phytolacca is usually made from the roots of Phytolacca acinosa and P. esculenta, but the invasive plant P. americana (American pokeweed) is also widely used. Different types of medicinal products made with Phytolacca are available, as well as various types of Phytolacca extracts, showing a range of pharmacological activities including antioxidant, anti-inflammatory, anti-parasitic, antifungal, anticancer, and insecticidal effects. The marked anti-inflammatory activity of Phytolacca extracts supports its use in treating diseases such as arthritis, nephritis, and rheumatism, as well as in combatting cancer. Several bioactive natural products have been identified from Phytolacca, including glycosylated saponins such as esculentosides and phytolaccosides, as well as a few flavones (cochliophilin A) and phytosterols (α-spinasterol), which contribute to Phytolacca's anti-inflammatory and/or anticancer effects. A quality evaluation of Phytolacca-based extracts and products is highly recommended; nevertheless, the use of Phytolacca can be encouraged to help regulate cytokine production and combat inflammatory diseases.